2009
DOI: 10.1590/s1516-14392009000100015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, thermal and morphological properties of glutaraldehyde crosslinked bovine pericardium followed by glutamic acid treatment

Abstract: Major problems with valve bioprostheses are associated with progressive structural deterioration and calcification, directly associated with the use of glutaraldehyde (GA). This work describes the effects of GA processing and borate/glutamic acid buffer treatment on the mechanical, thermal and morphological properties of 0.5% GA crosslinked bovine pericardium (BP). The results showed that while the treatment of 0.5% GA crosslinked BP with borate/glutamic acid significantly improves the mechanical properties, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Regarding the accelerated durability test, no signs of morphological changes (laceration or rupture) of the leaflets in any of the tested valves were observed, suggesting that there is some flexibility in morphological BP for the behavior of the valve, taking into account the differences found for different treatments. A previous study (20) showed that despite differences in dimpling of the collagen matrix, the fibrillar structure of the collagen is preserved.…”
Section: Resultsmentioning
confidence: 94%
“…Regarding the accelerated durability test, no signs of morphological changes (laceration or rupture) of the leaflets in any of the tested valves were observed, suggesting that there is some flexibility in morphological BP for the behavior of the valve, taking into account the differences found for different treatments. A previous study (20) showed that despite differences in dimpling of the collagen matrix, the fibrillar structure of the collagen is preserved.…”
Section: Resultsmentioning
confidence: 94%
“…Experimental mechanical details from uniaxial test 28 and thermal properties (measured using shrinkage temperature) 29 have been published previously 25 and provided in the Supporting Information section of this article.…”
Section: Methodsmentioning
confidence: 99%
“…The use of glutamic acid for neutralization of free aldehyde groups in BP/GA tissues with proposed manufacture of medical devices has not been widely reported in the literature studies 14,16,23,25‐27 . Some of them were performed under different sets of conditions 14,16,25,27 and in other studies 23,26 with similar protocols compared to the present research work. However, these previous reports did not describe any analysis of physical properties and clinical animal model studies, which are highly dependent on processing condition and had direct effects on the development of new BHVs with better performance.…”
Section: Introductionmentioning
confidence: 91%
“…Considering cross-linking degree of materials, we should reduce the concentration of GA as much as possible. The scaffold possessing suitable mechanical properties could be easily processed into different shapes and sizes and match particular application, such as cell culture scaffold, surgical dressing and organ filler [35,36].…”
Section: Rheological Characterizationmentioning
confidence: 99%